MORPHOLOGICAL DIAGNOSIS OF FAT EMBOLISM IN COMBINED TRAUMAS WITH FATAL OUTCOMES - Suxrob B. Sultanov; Ibragim I. Bakhriev (Central Asian Journal of Medicine, 2024)
The technocratic path of societal development leads to a steady increase in injuries and the escalation of all aspects of traumatic diseases. One of the early severe complications of musculoskeletal injuries is traumatic fat embolism. At the same time, the clinical manifestations of fat embolism in combined injuries are complicated by traumatic shock, traumatic brain injury, and traumatic respiratory failure of various causes. To date, the diagnosis of fat embolism remains a complex and completely unresolved problem, as fat embolism does not have a clear clinical picture and pathognomonic symptoms. Furthermore, forensic diagnosis of fat embolism is considered macroscopically complex, and a definitive conclusion can only be made through microscopic examination of internal organs (lungs, brain, kidneys, and heart).